Cervical radiculitis presenting as shoulder pain: frequency and results of multidisciplinary care. Issue 5 (September 2015) - Roberson, Troy A.; Jew, Nicholas B.; Azar, Frederick M.; Mauck, Benjamin M.; Dockery, John D.; Throckmorton, Thomas W.
Abstract : Background: Although cervical radiculitis is a well-known cause of referred shoulder pain, there is little information concerning its frequency and treatment. Methods: Retrospective review of the records of all new patients presenting to a single orthopaedic shoulder surgeon at a tertiary referral center from 2009 to 2012 identified 1169 patients with a chief complaint of shoulder pain; 60 (4%) with an isolated diagnosis of cervical radiculitis were included in the study; 48 were available for follow-up evaluation. If conservative therapy failed, MRI was done, followed by cervical epidural corticosteroid injection by a physiatrist (11 patients); three with persistent symptoms had anterior cervical fusion. Visual analog pain scores (VAS) were recorded at the initial visit, and VAS and National Disability Index Questionnaire (NDIQ) scores were obtained at a minimum of 1 yr. Results: Of 1169 patients with a chief complaint of shoulder pain, 60 (4%) were diagnosed with isolated cervical radiculitis. Of 48 available for follow-up evaluation, 34 were treated conservatively, 11 had cervical epidural injections, and three required anterior cervical discectomy and fusion (ACDF). At mean follow-up of 27 mo, the average overall pain score was 2 compared to 5.2 at the initial visit ( P <0.0001). The differences between initial and follow-up VAS scores demonstrated improvements with all three treatments. Fifteen patients reported no disability, and 32 reported minimal disability. Conclusions: These findings suggest that, if correctly diagnosed and treated, patients with cervical radiculitis presenting as shoulder pain can obtain marked reductions in pain and disability with a step-wise multidisciplinary treatment strategy.